Explanation of the Evidences and Documents of the Semantic Quasi System (Regularity, Discipline) of the Holy Qur'an - Hossein Jeddi; Hassan Naqizadeh; Abbas Esmailizadeh (آموزه‌های قرآنی)
One of the linguistic aspects of the Qur'anic text, which has confirmed the miraculous and revelatory of this Divine word is the system of semantics and intertextual relationships at different levels of concepts, verses and chapters (sūrah). Adopting this method of orderliness (regularity, discipline), which can be referred to as the reticulated order of the Qur'anic text, brings many functions in interpretive achievements. On the other side, the necessity of resorting to a comprehensive approach and forming a Quran-based regularity quasi system requires an intra-religious basis finding. This article, by adopting a subsequent approach, from the passage of inquisitiveness (questioning) in Qur'anic uses, in addition to reviewing two similar interpretations of Qur'anic, i.e. explaining the brightness of the implication of [mathānī] (Arabic: مَثانی, consistent with itself, a scripture [composed] of similar motifs) (az-Zomar/23) on the contextual relations of the Qur'an and the coordination of its verses in the main domain of the text (an-Nisa/82) by relying on some of the ḥadiths of the Infallibles (AS) has explained the intra-religious arguments of the semantic quasi system of the Noble Qur'an. Therefore, these reticulated connections can be presented not only in the dimensions of conceptual and thematic, but also in the range of [between verses] verses and between chapters of the Holy Qur'an in the Qur'anic text.